Effect of Forest Ecotourism on Socioeconmic Conditions of Local Community - Kausar , Rukhsana; Mirza, Sarwat N; Akhtar, Saira (Asian Journal of Agriculture and Rural Development, 2015)
Pakistan is having scarcity of forests, with the total area covered under forest being 5%, while it must be 25%. Inspite of the fact that we have to protect and expand our forests, many other alternative land cover and land use practices are going to be more common. Current study is a part of that effort. To have panel discussion and interviews of activists and key persons of the rural areas in the vicinity of major ecotourism spots that is Mall, Bhurban, Patriata 2-3 workshops were arranged in which a semi structured questionnaire was followed to assess the role of ecotourism in the livelihood and socioeconomic conditions of the local community. This study shows that most of the people get 5000-10000 (49.30-98.60), rupees increase in the income per month while some earn 11000-20000 (108.45-197.19). Even (4%, who have rented houses and restaurants) think that the raise of income is PKR 21000-50000(207.5-492.98). The local villager’s perceptions about the ecological negative and positive aspects of ecotourism show that the forest based tourism has more positive effects on the lives of people as well as for biodiversity and nature conservation, as it develops the wildlife reserves, promotes the awareness of forests, environment and biodiversity, it also proves a good source of knowledge and motivation of visitors that increases the stewardship, to love and conserve natural resources.